R S AGGARWAL AND V AGGARWAL Solutions for Class 10 Maths Chapter 2 - Polynomials

Page / Exercise

Chapter 2 - Polynomials Ex. 2A

Solution 1

Solution 2

Solution 3

Solution 5

We have


Solution 6

Solution 7

Solution 8

Solution 9

Solution 10

Solution 12

Let

 

 

Solution 14

 

Solution 15

Solution 16

Solution 18

Solution 20

Solution 21

Solution 4

2x2 - x - 6 = 0

⇒ 2x2 - 4x + 3x - 6 = 0

⇒ 2x(x - 2) + 3(x - 2) = 0

⇒ (x - 2)(2x + 3) = 0

⇒ (x - 2) = 0 or (2x + 3) = 0

So, the zeroes of the given quadratic polynomial are 2 and

Sum of the zeros

Product of the zeros

Solution 11

5x2 + 10x = 0

⇒ 5x(x + 2) = 0

⇒ 5x = 0 or (x + 2) = 0

x = 0 or x = -2

So, the zeroes of the given quadratic polynomial are 0 and -2.

Sum of the zeros

Product of the zeros

Solution 13

p(x) = 2x2 + 5x + k

Here, a = 2, b = 5 and c = k

α + β =  and αβ =

α2 + β2 + αβ =  …. Given

Solution 17

Let α = 2 and β = -6

Sum of zeros = α + β = 2 + (-6) = -4

Product of zeros = αβ = 2(-6) = -12

So, the required quadratic polynomial is

x2 - (α + β)x + αβ = x2 + 4x - 12

Here, a = 1, b = 4 and c = -12

Sum of the zeros

Product of the zeros

Solution 19

Chapter 2 - Polynomials Ex. 2B

Solution 1
Solution 2

Solution 3

Solution 4

Solution 5

Solution 6

Solution 7

Solution 8

Solution 9

Solution 10

Here, remainder = 2x + 3 = px + q

p = 2 and q = 3

Solution 11

Solution 12

Solution 13

1

Solution 14



Solution 15

 

Solution 16


Solution 17


Solution 21

f(x) = 3x3 + 16x3 + 15x - 18

 is one zero of f(x).

 is a factor of f(x).

⇒ (3x - 2) is also a factor of f(x).

Solution 22

Here, f(x) = 2x4 - 3x3 - 3x2 + 6x - 2

1 and  are two zeros of f(x).

 is a factor of f(x).

 is a factor of f(x).

Solution 18


Solution 19

Here, f(x) = x4 + x3 - 14x2 - 2x + 24

Since, √2 and -√2 are two zeros of f(x)

⇒ (x - √2) and (x + √2) is a factor of f(x).

⇒ (x - √2) and (x + √2) = x - 2 is a factor of f(x).

Solution 20

Here, f(x) = 2x4 - 13x3 + 19x2 + 7x - 3

Let α = (2 + √3) and β = (2 - √3). Then,

α + β = (2 + √3).+ (2 - √3) = 4

αβ = (2 + √3).(2 - √3) =4 - 3 = 1

So, the quadratic polynomial whose roots are α and β is given by

x2 - (α + β)x + αβ = x2 - 4x + 1

x2 - 4x + 1 is a factor of f(x).

Solution 23



Chapter 2 - Polynomials Ex. 2C

Solution 1

Solution 2

Solution 3

Solution 4

Solution 5

Solution 6

Solution 7

Solution 8

Solution 9

Solution 10

Solution 11

Solution 12

Solution 13

Solution 14

Solution 15

Solution 16

Solution 17

If f(x) and g(x) are any two polynomials with g(x) ≠ 0, then we can always find polynomials q(x) and r(x) such that f(x) = q(x)g(x) + r(x),

where r(x) = 0 or degree r(x) < degree g(x).

Solution 18

Solution 19

Solution 20

Solution 21

Solution 22

Solution 23

Solution 24

Solution 25

Chapter 2 - Polynomials MCQ

Solution 1

Correct answer: (d)

An expression of the form p(x) = a0 + a1x + a2x2 + ….. + anxn, where an ≠ 0, is called a polynomial in x of degree n.

Here, a0, a1, a2, ……, an are real numbers and each power of x is a non-negative integer.

Solution 2

Correct answer: (d)

An expression of the form p(x) = a0 + a1x + a2x2 + ….. + anxn, where an ≠ 0, is called a polynomial in x of degree n.

Here, a0, a1, a2, ……, an are real numbers and each power of x is a non-negative integer.

Solution 3

Solution 4

Solution 5

Solution 6

Solution 7

Solution 8

Solution 9

Solution 10

Solution 11

Solution 12

Solution 13

Solution 14

Solution 15

Solution 16

Solution 17

Solution 18

Solution 19

Solution 20

Solution 21

Solution 22

Solution 23

Solution 24

Solution 25

Solution 26

Solution 27

Solution 28

Chapter 2 - Polynomials FA

Solution 1

Solution 2

Solution 3

Solution 4

Solution 5

Solution 6

Solution 7

Solution 8

Solution 9

Solution 10

Solution 11

Solution 12

Solution 13

Solution 14

Solution 15

Solution 16

Solution 17

Solution 18

Solution 19

  

Solution 20